Stereotactic radiofrequency thermocoagulation application in the anterior limbs of patients' internal capsules in treating intractable tic disorders. (1st January 2020) - Li, Yu-Hui; Zhao, Kai; Wang, Mei-Qing; Wang, Jing; Gao, Bu-Lang
Abstract: Purpose: To investigate the effect of applying stereotactic radiofrequency thermocoagulation in the anterior limbs of patients' internal capsules in treating intractable tic disorders. Materials and methods: Patients diagnosed with intractable tic disorders were prospectively enrolled and treated using stereotactic radiofrequency thermocoagulation in the anterior limbs of the internal capsules. Periprocedural complications, effects, and follow-up outcomes were then analyzed. Results: Fifty patients were enrolled, including 38 with Tourette syndrome and 12 with persistent refractory vocal or motor tic disorders. The radiofrequency thermocoagulation procedure was performed successfully in all patients. Five participants (10%) experienced periprocedural complications, including one having a slight hemiplegia, two developing fevers (4%), and two developing urination disorders (4%). The participants underwent a follow-up for 12 months, with excellent effects being achieved in 23 patients (46%), prominent results in 13 (26%), good results in 10 (20%), and invalid results in 4 (8%), reaching an efficacy rate of 92% (46/50). Thirty-six patients experienced excellent and prominent effects, with no additional management after the radiofrequency ablation being needed, achieving a success rate of 72%. After radiofrequency thermocoagulation, the Yale Global Tic Severity Scale (YGTSS) scores were significantly reduced ( p  < .01) when compared with those before the procedure. Following this procedure, participants' serum dopamine levels (SDA) significantly decreased ( p  < .05), while their serotonin levels were significantly elevated ( p  < .05) when compared to the measurements taken before the procedure. Conclusion: Stereotactic radiofrequency thermocoagulation applied to the anterior limbs of patients' internal capsules may be effective for treating intractable tic disorders, without risk of serious complications.